THE EFFECT OF LEADERSHIP STYLE AND MOTIVATION ON PERFORMANCE OF BANK BTPN EMPLOYEES, SUNGGUMINASA BRANCH, GOWA REGENCY - Muh Ramli; Sultan Sarda (Universitas Muhammadiyah Makassar, 2021)
Research Entrepreneurship Study Program Faculty of Business Mega Buana Palopo University. This research aims to find out the leadership style and motivation to affect the performance of employees of Bank BTPN Sungguminasa Branch, Gowa Regency. The type of research used is quantitative. The data collection was conducted by distributing questionnaires to 32 respondents of Bank BTPN Sungguminasa Branch in Gowa Regency. This study uses multiple linear regression analysis methods. The results of this study show that, based on t statistical test, t calculated value for leadership style variable (X1) 3,233 t table 1,695 and significant value 0.002 0.05. While motivation variable (X2) 5,637 t table 1,695 and significant value 0.000 0.05. Therefore, it is concluded that the leadership style and motivation significantly affect the performance of employees of Bank BTPN Sungguminasa Branch in Gowa Regency